Temporal Vestibular Deficits in synaptojanin 1 (synj1) Mutants - Gao, Yan; Nicolson, Teresa (Frontiers in Molecular Neuroscience, 2021)
The lipid phosphatase Synaptojanin 1 (Synj1) is required for the disassembly of clathrin coats on endocytic compartments. In neurons such activity is necessary for the recycling of endocytosed membrane into synaptic vesicles. Mutations in zebrafish synj1 have been shown to disrupt the activity of ribbon synapses in sensory hair cells. After prolonged mechanical stimulation of hair cells, both phase locking of afferent nerve activity and the recovery of spontaneous release of synaptic vesicles are diminished in synj1 mutants. Presumably as a behavioral consequence of these synaptic deficits, synj1 mutants are unable to maintain an upright posture. To probe vestibular function with respect to postural control in synj1 mutants, we developed a method for assessing the vestibulospinal reflex (VSR) in larvae. We elicited the VSR by rotating the head and recorded tail movements. As expected, the VSR is completely absent in pcdh15a and lhfpl5a mutants that lack inner ear function. Conversely, lhfpl5b mutants, which have a selective loss of function of the lateral line organ, have normal VSRs, suggesting that the hair cells of this organ do not contribute to this reflex. In contrast to mechanotransduction mutants, the synj1 mutant produces normal tail movements during the initial cycles of rotation of the head. Both the amplitude and temporal aspects of the response are unchanged. However, after several rotations, the VSR in synj1 mutants was strongly diminished or absent. Mutant synj1 larvae are able to recover, but the time required for the reappearance of the VSR after prolonged stimulation is dramatically increased in synj1 mutants. Collectively, the data demonstrate a behavioral correlate of the synaptic defects caused by the loss of synj1 function. Our results suggest that defects in synaptic vesicle recycling give rise to fatigue of ribbons synapses and possibly other synapses of the VS circuit, leading to the loss of postural control.